2015
DOI: 10.1038/onc.2014.455
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER3 by interfering with its Sec61-mediated cotranslational insertion into the endoplasmic reticulum

Abstract: There is increasing evidence implicating HER3 in several types of cancer. But the development of targeted therapies to inactivate HER3 function has been a challenging endeavor. Its kinase domain functions in allostery not catalysis, and the classical ATP-analog class of tyrosine kinase inhibitors fail to inactivate it. Here we describe a novel approach that eliminates HER3 expression. The small-molecule cotransin CT8 binds the Sec61 translocon and prevents the signal peptide of the nascent HER3 protein from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 49 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…3), a highly substrateselective cotransin as a potent inhibitor of expression of the cancer-associated cell surface pseudokinase HER3, which was found to contain a highly cotransin-sensitive signal peptide. 21 The reduced HER3 expression upon treatment of BT474 breast cancer cells with cotransin results from increased proteasomal turnover induced by the cytosolic displacement of the HER3 membrane protein. It is interesting that HER3 among the four signal peptide-containing HER family members is uniquely sensitive to CT8, and this opens up new therapeutic strategies to control HER activity in breast cancer.…”
Section: Cotransinsmentioning
confidence: 99%
See 1 more Smart Citation
“…3), a highly substrateselective cotransin as a potent inhibitor of expression of the cancer-associated cell surface pseudokinase HER3, which was found to contain a highly cotransin-sensitive signal peptide. 21 The reduced HER3 expression upon treatment of BT474 breast cancer cells with cotransin results from increased proteasomal turnover induced by the cytosolic displacement of the HER3 membrane protein. It is interesting that HER3 among the four signal peptide-containing HER family members is uniquely sensitive to CT8, and this opens up new therapeutic strategies to control HER activity in breast cancer.…”
Section: Cotransinsmentioning
confidence: 99%
“…The authors further showed that CT8 efficiently enhances the efficiency of existing HER2 therapies in BT474 breast cancer cells. 21 Further, many studies have identied importance of the role of the ER secretory pathway for replication of different aviviruses and in one of these studies Sec61 was identied as a host factor required for growth and infectivity of several viruses including inuenza, HIV and dengue. 22 Treatment of cells with noncytotoxic concentrations of CT8 potently inhibited three different strains of HIV.…”
Section: Cotransinsmentioning
confidence: 99%
“…These initial studies reported inhibition of VCAM-1, P-selectin, angiotensinogen, β-lactamase, and corticotropin-releasing factor receptor 1 (CRF-R-1). Later studies also identified endothelin B receptor [ 37 ], human epidermal growth factor receptor 3 [ 38 ] and tumor necrosis factor alpha (TNFα) [ 39 ], a type II integral membrane protein with uncleaved signal anchor, as targets of cotransin.…”
Section: Inhibitors Of Translocon Gatingmentioning
confidence: 99%
“…They are mostly antibody-based, blocking ligand binding to HER3, or preventing its dimerisation with other EGFR receptors or triggering its internalisation [ 20 , 28 , 29 ]. A very few pharmacological approaches to targeting HER3 have been developed, essentially interfering with its expression [ 30 ], including modified ATP-competitive molecules binding to HER3 to induce its proteasomal degradation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%